Perception, strategy and interest: the state and foreign policy in India after independence - Mitra, Subrata Kumar (The impact of Asian powers on global developments, 2004)
After decades of obscurity and benign neglect by security analysts, South Asia has suddenly loomed large on the radar screens of the Western security establishment.